Cold-induced stress responses during a self-rescue exercise from accidental immersion in ice water in military personnel - Beres, Yannick; Lechner, Raimund; August, Elias; Koch, Andreas; Radermacher, Peter; Kulla, Martin; Staps, Enrico (Frontiers in Physiology, 2025)
IntroductionCold-water immersion induces autonomic stress responses including sympathetic cold shock and parasympathetic diving and trigeminovagal reflexes, potentially leading to arrhythmias or bronchospasm. Another important complication of cold-water immersion is hypothermia. This study evaluates physiological responses during ice-self-rescue training to assess safety and temperature monitoring accuracy.MethodsWe conducted a prospective observational cohort study of 80 healthy Mountain Infantry soldiers during a standardized ice-self-rescue training in Norway (air temperature −10 °C). Participants underwent partial immersion (0.5 °C water) resulting in transitory submersion (<5 s). They were equipped with continuous 3-lead ECG (n = 34) spirometry (n = 26); and core temperature monitoring (ingestible telemetric capsule (n = 23) versus bilateral tympanic thermometry with and without ear channel occlusion (n = 34). Primary outcomes included cardiac rhythm changes, lung function parameters and temperature measurement agreement.ResultsECG analysis revealed significant post-immersion tachycardia (median increase of 17 bpm, p = 0.03) and increased RR-interval variability (+90 ms, p < 0.01), without malignant arrhythmias. Spirometry showed no clinically significant changes in FVC or FEV1 and peak expiratory flow. Tympanic readings underestimated core temperature post-immersion (median difference −2.8 °C versus capsules, p < 0.01), with ear canal occlusion did not improve accuracy (p = 0.15).ConclusionSupervised cold-water immersion during military training exercise elicited expected autonomic stress responses without life-threatening complications in healthy soldiers. These findings suggest structured cold-water training can be safely conducted for fit individuals. Tympanic thermometry proved unreliable following immersion, even after ear channel occlusion. Ingestible capsule thermometry may be a viable approach if invasive measurement is not possible.Clinical Trial RegistrationThis trial was registered under “Cold induced stress reactions during cold water immersion” in the German Clinical Trial Register (DRKS) under the registration number DRKS00032345 (https://www.drks.de/search/de/trial/DRKS00032345/details).